2011
DOI: 10.2183/pjab.87.53
|View full text |Cite
|
Sign up to set email alerts
|

Development of modified nucleosides that have supremely high anti-HIV activity and low toxicity and prevent the emergence of resistant HIV mutants

Abstract: An idea to use 4′-C-substituted-2′-deoxynucleoside derivatives was proposed based on a working hypothesis to solve the problems of existing acquired immune deficiency syndrome chemotherapy (highly active antiretroviral therapy). Subsequent studies have successfully proved the validity of the idea and resulted in the development of 2′-deoxy-4′-C-ethynyl-2-fluoroadenosine and 2′-deoxy-4′-C-ethynyl-2-chloroadenosine, nucleoside reverse transcriptase inhibitors, which have supremely high activity against all human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In addition, as described, the present study showed that EFdA and related NRTIs with the 4′-ethynyl or 4′-cyano moiety showed very potent activity against HIV-1 M184V and HIV-1 EFdA R ; however, related compounds with other moieties such as the 4′-methyl moiety did not show any activity. The result was also consistent to the previous studies for other 4′-modified NRTIs (Kohgo et al, 1999; Ohrui et al, 2011). Taken together, this finding suggests that the structure of the 4′-moiety of NRTIs determines the activity of the NRTIs not only against HIV-1 or HBV but also against drug-resistant HIV-1 variants.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, as described, the present study showed that EFdA and related NRTIs with the 4′-ethynyl or 4′-cyano moiety showed very potent activity against HIV-1 M184V and HIV-1 EFdA R ; however, related compounds with other moieties such as the 4′-methyl moiety did not show any activity. The result was also consistent to the previous studies for other 4′-modified NRTIs (Kohgo et al, 1999; Ohrui et al, 2011). Taken together, this finding suggests that the structure of the 4′-moiety of NRTIs determines the activity of the NRTIs not only against HIV-1 or HBV but also against drug-resistant HIV-1 variants.…”
Section: Discussionsupporting
confidence: 93%
“…The introduced phosphate ester could be cleaved in cells to generate phosphate monoester. EdA ( 2 ) was easily hydrolyzed by adenosine deaminase to generate the corresponding inactive inosine derivative [6,11,37]. However, EdAP, which has the same scaffold as EdA, except in the case of cyclosaligenyl phosphate ester, exhibited anti-influenza activity.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitors should work against several subtypes of influenza A viruses and be tolerated by a drug-resistant mutant because it is highly conserved in all influenza subtypes and is essential to the viral life cycle. We have previously reported on a highly potent antihuman immunodeficiency virus (HIV) nucleoside derivative called 4′-ethynyl-2-fluoro-2′-deoxyadenosine (EFdA, 1 , Figure 1) [5,6,7,8,9,10,11,12,13]. EFdA is an adenosine derivative armed with an ethynyl group at the 4′-position, which prevents the extension of a nucleotide at 3′-OH because of its steric hindrance by the 4′-substituent, providing features of a viral DNA chain terminator and a reverse transcriptase inhibitor [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Various fatty acid conjugates of AZT (13D), d4T (14A-D), and 3TC (15B-D and 16B and C) were prepared. 14,15 Several such derivatives have progressed, including the thymidine derivative BMS-986001 (festinavir, 18) and 2 0 -deoxy-4 0 -C-ethynyl-2-fluoroadenosine (EFdA, 19). Another approach investigated 1,3-diacylglycerol conjugates of AZT 5 0monophosphate in which the conjugate 17 demonstrated anti-HIV activity similar to the parent nucleoside AZT but suffered from chemical and enzymatic instability.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…14,15 Several such derivatives have progressed, including the thymidine derivative BMS-986001 (festinavir, 18) and 2 0 -deoxy-4 0 -C-ethynyl-2-fluoroadenosine (EFdA, 19). 14 19 also showed activity against M184V and multidrug-resistant HIV-1 strains and had minimal effect on human mitochondrial DNA polymerase γ, with an EC 50 ¼ 10 μM, or human DNA polymerases α and β. It showed equivalent activity against wild-type HIV-1 and HIV-1 with K65R and Q151M RT mutations, but reduced potency against multidrug-resistant isolates.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%